Political learning in territories of exclusion, conflict and popular organization (research notes) - Paulo J. Krischke (Ciências Sociais Unisinos)
This paper discusses some interfaces between the approaches to political learning, and their reference to situations of social exclusion, conflict and popular organization. The first part of the paper discusses the approach to the study of political learning among the elites; the second part examines approaches to research of political culture among the masses; and the third part outlines an alternative approach to political learning derived from Jürgen Habermass theory of communicative action. In the paper these approaches are applied to the study of a territory of exclusion, conflict, and popular organisation (a group of favelas in downtown Florianópolis, Santa Catarina, Brazil). Finally, the paper outlines some procedures to achieve a more general understanding of political learning